Reptilia, Squamata, Serpentes, Scolecophidia, Anomalepididae, Liotyphlops cf. ternetzii (Boulenger, 1896): first family record for the state of Ceara, Brazil. - Loebmann, Daniel [UNESP] (2009)
Universidade Estadual Paulista, Instituto de Biociencias, Laboratorio de Herpetologia, Av. 24 A, 1515, Bairro Bela Vista, CEP 13506-900, Rio Claro, SP, Brazil